THE INVESTIGATION OF THE ANTIPROLIFERATIVE, ANTIMIGRATION AND ANTIOXIDANT EFFECTS OF TAURINE, CAPSAICIN, MELATONIN AND BETA CAROTEN ON L929 HEALTHY CELLS AND MCF-7 BREAST CANCER CELLS - Yüce, Hande; Türkmen, Neşe Başak; Özek, Dilan Aşkın; Ünüvar, Songül (University of Ankara, 2022)
Objective: The aim of this study was to evaluate the antiproliferative, antimigration and antioxidant activities of antioxidant substances such as taurine, capsaicin, melatonin and beta carotene on human breast cancer cells. Material and Method: In this study, taurine, capsaicin, melatonin and beta carotene L929 were applied to healthy fibroblast cells and MCF-7 breast cancer cells. The antiproliferative effect of the compounds was determined by the MTS [3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4sulphophenyl)-2H-tetrazolium] test at 24 and 48 hours. Cells were cultured in Dulbecco's Modified Eagles Medium (DMEM) and treated with different concentrations for two consecutive days. The effect of compounds on cell migration was evaluated at 24 hours using the wound healing assay. The wound healing test was used to measure the in vitro metastatic ability of cells. Total antioxidant levels (TAS) and total oxidant levels (TOS) were determined using commercial kits. Result and Discussion: All compounds decreased cell viability in malignant cells in a concentration- and time-dependent manner compared to healthy cells. The results of the wound closure area showed that treatment with the compounds improved cellular migration, which significantly accelerated wound closure. The results showed that all compounds markedly inhibited the migratory ability of MCF-7 cell lines at 48 hours. Although all compounds showed antioxidant effects, beta carotene was observed to have antioxidant effects on MCF-7 cells at almost all doses. © 2022 University of Ankara. All rights reserved.
TAURİN, KAPSAİSİN, MELATONİN VE BETA KAROTENİN L929 SAĞLIKLI HÜCRELER VE MCF-7 MEME KANSERİ HÜCRELERİ ÜZERİNDEKİ ANTİPROLİFERATİF, ANTİMİGRASYON VE ANTİOKSİDAN ETKİLERİNİN ARAŞTIRILMASI
Keywords: Beta carotene; Breast cancer; Capsaicin; Melatonin; Taurine